Post Stroke Hydrocephalus: A Case Report - Karki, Mohan; Roka, Yam Bahadur (Birat Journal of Health Sciences, 2021)
Hydrocephalus in case of hemorrhagic stroke with intravetricular extension is common complication, but without intraventricular extension is rare. However, we rarely find hydrocephalus following resolved hemorrhagic stroke. We present a case of communicating hydrocephalus in 65 year female who presented with left sided weakness, disoriented and loss of consciousness since few weeks. Patient was managed with ventriculoperitoneal (VP) shunt. We report this unusual case with pertinent literature.